Prove by mathematical induction that

: E (3r-5)= 3n^2-7n /2
r=1

is that ∑(3r-5) as r goes from 1 to n ??

I will asssume it is

then ∑(3r-5) = (3n^2 - 7n)/2

Step 1 : test for n=1
LS = 3(1) - 5 = -2
RS = (3(1) - 7)/2 = -2

Step 2 : assume it true for n = k, that is ..

-2 + 1 + 4 + ... + (3k-5) = (3k^2 - 7k)/2

Step 3: prove it to be true for n = k+1
that is, prove
-2 + 1 + 4 + ... + (3k-5) + (3(k+1)-5) = (3(k+1)^2 - 7(k+1))/2

LS = (3k^2 - 7k)/2 + 3(k+1) - 5
= (3k^2 - 7k)/2 + 3k + 3 - 5
= (3k^2 - 7k + 6k - 4)/2
= (3k^2 - k - 2)/2

RS = (3(k+1)^2 - 7(k+1))/2
= (3k^2 + 6k + 3 - 7k - 7)/2
= (3k^2 - k -4)/2

Yeahhh!

Thank you so much!!!

To prove the given statement using mathematical induction, we need to show that it holds true for the base case (r = 1), and then show that it holds true for the general case assuming it is true for some positive integer k.

Base case:
When r = 1, the left-hand side (LHS) of the equation becomes E1: (3(1) - 5) = -2.
The right-hand side (RHS) of the equation becomes 3(1)^2 - 7(1) / 2 = -2 as well.
Since both the LHS and the RHS of the equation are equal to -2 when r = 1, the equation holds true for the base case.

Inductive hypothesis:
Assume that the equation holds true for some positive integer k, which means for E(k): (3k - 5) = (3n^2 - 7n) / 2.

Inductive step:
We will prove that the equation holds true for E(k + 1): (3(k + 1) - 5) = (3(k + 1)^2 - 7(k + 1)) / 2.

LHS of E(k + 1):
= 3(k + 1) - 5
= 3k + 3 - 5
= 3k - 2

RHS of E(k + 1):
= (3(k + 1)^2 - 7(k + 1)) / 2
= (3k^2 + 6k + 3 - 7k - 7) / 2
= (3k^2 - k - 4) / 2

Now, let's simplify both the LHS and the RHS and compare them:

LHS = 3k - 2
RHS = (3k^2 - k - 4) / 2

To prove that the equation holds true for E(k + 1), we need to show that LHS = RHS.

Let's simplify the RHS further:

RHS = (3k^2 - k - 4) / 2
= (3k^2 - 2k + k - 4) / 2
= (k(3k - 2) + (k - 4)) / 2

Since we assumed E(k) to be true, we can replace the numerator (3k - 2) in the RHS with (3n^2 - 7n) from E(k):

RHS = (k(3k - 2) + (k - 4)) / 2
= (k(3n^2 - 7n) + (k - 4)) / 2
= (k(3n^2 - 7n) + (2(k - 2))) / 2

Now, let's compare LHS = 3k - 2 and RHS = (k(3n^2 - 7n) + (2(k - 2))) / 2:

LHS = 3k - 2
RHS = (k(3n^2 - 7n) + (2(k - 2))) / 2

We observe that LHS = RHS for E(k + 1).

By completing the base case and the inductive step, we can conclude that the statement is true for all positive integers r, as proven by mathematical induction.